2017
DOI: 10.1002/ana.24871
|View full text |Cite
|
Sign up to set email alerts
|

Eye‐tracking–based assessment suggests preserved well‐being in locked‐in patients

Abstract: We assessed quality of life (QoL) and psychological well-being in patients with amyotrophic lateral sclerosis-induced locked-in state and their next of kin in a fully unbiased manner using eye-tracking computer systems. Eleven of 30 screened patients and 9 next of kin completed study procedures. Patients reported good QoL, which appeared to be at the cost of the QoL of their next of kin. Next of kin rated their own or patients' QoL similarly, but they identified different areas as important as compared with pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(66 citation statements)
references
References 25 publications
3
61
0
2
Order By: Relevance
“…The assumption of a positive effect on Qol is further supported by the findings that HT-AAC-use serves as an active coping mechanism, helps patients to express emotions and personality and to maintain social roles, participation in family and community and even employment ( 21 , 43 ). These results are confirmed by the first study evaluating the association between QoL and ETCS use in ALS-patients in the locked-in-state (LIS) in a fully caregiver-independent manner by using ETCS-based assessment ( 44 ). Patients reported on average a high QoL and the study suggests that ETCS preserve patient autonomy and therefore psychosocial wellbeing particularly by enabling social activities, which patients named as the most important area of life for their QoL.…”
Section: Advantages and Promises Of Ht-aac In Palliative Carementioning
confidence: 56%
“…The assumption of a positive effect on Qol is further supported by the findings that HT-AAC-use serves as an active coping mechanism, helps patients to express emotions and personality and to maintain social roles, participation in family and community and even employment ( 21 , 43 ). These results are confirmed by the first study evaluating the association between QoL and ETCS use in ALS-patients in the locked-in-state (LIS) in a fully caregiver-independent manner by using ETCS-based assessment ( 44 ). Patients reported on average a high QoL and the study suggests that ETCS preserve patient autonomy and therefore psychosocial wellbeing particularly by enabling social activities, which patients named as the most important area of life for their QoL.…”
Section: Advantages and Promises Of Ht-aac In Palliative Carementioning
confidence: 56%
“…All available epidemiological and empirical studies investigating quality of life and depression in ALS have found a sufficient, even good, quality of life (Lulé et al 2009(Lulé et al , 2013 and positive mood and emotional processing at all stages of the disease. Even in LIS (Linse et al 2017) when only assisted communication via computer menus with eye movements is possible. Before entering the LIS state, communication with more reliable muscle responses such as finger twitches and eye movements is still possible.…”
Section: Effects Of Emotional Factors and Quality Of Lifementioning
confidence: 99%
“…So gibt es mehrere Studien (n: 9-76 Patienten), die eine zufriedenstellende bis gute Lebensqualität bei ALS-Patienten berichten [42][43][44],wasgegendieNotwendigkeitspezifischerInterventionen spräche. Darüber hinaus weisen empirische Ergebnisse darauf hin, dass die Lebensqualität der Patienten von deren sozialer Umgebung häufigdeutlichschlechtereingeschätztwirdalsvondenPatienten selbst(n:89Patienten,86Pflegende,102gesundeKontrollpersonen) [45].…”
Section: Bedarf An Versorgungsangebotenunclassified
“…Darüber hinaus weisen empirische Ergebnisse darauf hin, dass die Lebensqualität der Patienten von deren sozialer Umgebung häufigdeutlichschlechtereingeschätztwirdalsvondenPatienten selbst(n:89Patienten,86Pflegende,102gesundeKontrollpersonen) [45]. Dennoch ist anzumerken, dass bei solchen Studien meist nur durchschnittliche Werte der Lebensqualität berichtet werden: So zeigen die oben genannten Studien, die zwar im Durchschnitt eine verhältnismäßig gute Lebensqualität der ALS-Patienten fanden, gleichzeitig auch einen hohen Anteil an Patienten mit klinisch bedeutsamerdepressiverSymptomatik,derzwischen28und48% lag [42][43][44]…”
Section: Bedarf An Versorgungsangebotenunclassified